Identification and Prioritization of Effective Factors on the Creation and Development of Industry Cluster of Rail Industries Using Network Analysis Technique - Yadegari, Reza; Rahmani, Kamaleddin; Modarres Khiyabani, Farzin (Brazilian Journal of Operations & Production Management, 2018)
Increased productivity and new investment are two methods for the development of industry, and one of the differences between advanced industrial countries and developing countries is to pay particular attention to development through increased productivity. In recent years, new models have been developed in the industry sector, dating to less than fifteen years; one of them is the model of industrial cluster development. Industrial clustering is being carried out today in almost every country in the world. In Iran, the industrial cluster issue is considered in scientific and decision-making centers, as well as in the development plans of the country. The purpose of this research was to identify and prioritize the effective factors on the development and creation of industry cluster of rail industries in the Markazi Province using the network analysis technique. In order to identify cluster creation factors, library studies and the Delphi method were used with the cooperation of the expert group. In the following, we examined the relative importance of these factors using the network analysis technique and the factors were prioritized by Super Decision Application. The results showed that the indicators of geographical concentration and environmental factors are included in the most important factors and the communication index is the least important factor in the creation and development of industrial clusters of rail industries in the Markazi Province.